The Influence of Social Responsibility on Profitability in the Southern African Banking Industry - Aliamutu, Kansilembo Freddy; Mkhize, Msizi Vitalis (Universitas Syiah Kuala, 2024)
Objective This study aims to examine the effect of social responsibility on profitability in the Southern African banking industry.Methodology The study utilized content analysis to evaluate financial statements, including measures of return on assets and return on equity, and social responsibility components based on International Accounting Principles. Panel data from 2015 to 2019 were used to assess the impact of social responsibility reporting on profitability. This paper regresses SR reporting on Profitability using panel data from 2015 to 2019.Results The standard deviation for banks in Mozambique (0.1916) was higher than that of banks in South Africa (0.0928) according to the SR_Dind variable. The lack of significance in the impact of environmental initiatives on profitability (1 = 0.001, P-value 0.1) may be attributed to Mozambique's underdeveloped status compared to South Africa. The larger size and significance of the SR_Dind coefficient for the entire sample suggest that the impact is more significant for South African banks (1 = 0.057 and 1 = 0.068, p 5%) than for Mozambique banks (2 = 0.049 and 2 = 0.051, p 5%).Research limitations/implications The study's focus on a small sample (the biggest 10 banks in every nation) makes it less intriguing than it could be if all banks had been included in the sample. The research significantly elucidates the relationship between SR reporting and profitability by throwing light on SR's behaviour in the banking industry, answering the unresolved problem relating SR reporting and profitability in the banking industry. The study may be used by lawmakers and shareholders to help explain how banks operate in these two nations.Novelty/Originality The study provides an original perspective on how voluntary Social Responsibility Commitment Report could help enhance profitability in the banking industry.